An analysis of native Dari speakers’ errors in university-level Dari and English writing - Naderi, Shamim (Kansas State University, 2010)
Writing well, especially in English, is an asset to anyone who aspires to succeed in the academic or other professional fields in this age of English as a lingua franca. Numerous scholars have investigated errors committed by English-as-a-foreign-language (EFL) learners. However, to date there is no empirical study on the error patterns displayed in native Dari speakers’ EFL writing in English and in Dari. The present study investigates error occurrences in 20 native Dari speakers’ English and Dari writing. These participants were English majors attending Balkh University, in Mazar-i-Sharif, Afghanistan. Most of the participants self-identified their English proficiency levels as “advanced.” The data were collected through convenience sampling of the students enrolled in EFL writing courses who voluntarily participated in two writing tasks of different levels of difficulty; they completed these first in English and then a week later in Dari. In order to observe any patterns, all spelling and word choice errors were identified by three independent judges (one Dari instructor at BU, one native-American-English-speaking graduate student in the English Department, and the author who is bilingual and works as an English instructor). All three worked separately initially and then discussed any discrepancies together in person (English) or via Skype (Dari), until they reached consensus. The analysis, concerning the three research hypotheses, supported these findings: (1) as predicted, the native Dari speakers committed a variety of errors similar to learners from previous studies; (2) as predicted, the participants made fewer errors in English than in Dari; and (3) counter to the hypothesis, the results indicated that the participants, when writing in Dari, demonstrated more errors in the simpler tasks; yet, the participants committed more errors in the more complex (versus simpler) English writing task, consistent with this hypothesis.
Keywords: Dari and English writing; English as a Second Language (ESL); English as a Foreign Language (EFL); Second language acquistion; Pedagogy; Analysis of native Dari speakers' errors; Language, Linguistics (0290); Language, Modern (0291)